HIV Latency - Siliciano, R. F.; Greene, W. C. (Cold Spring Harbor perspectives in medicine, 2011)
HIV-1 can establish a state of latent infection at the level of individual T cells. Latently infected cells are rare in vivo and appear to arise when activated CD4(+) T cells, the major targets cells for HIV-1, become infected and survive long enough to revert back to a resting memory state, which is nonpermissive for viral gene expression. Because latent virus resides in memory T cells, it persists indefinitely even in patients on potent antiretroviral therapy. This latent reservoir is recognized as a major barrier to curing HIV-1 infection. The molecular mechanisms of latency are complex and include the absence in resting CD4(+) T cells of nuclear forms of key host transcription factors (e.g., NFκB and NFAT), the absence of Tat and associated host factors that promote efficient transcriptional elongation, epigenetic changes inhibiting HIV-1 gene expression, and transcriptional interference. The presence of a latent reservoir for HIV-1 helps explain the presence of very low levels of viremia in patients on antiretroviral therapy. These viruses are released from latently infected cells that have become activated and perhaps from other stable reservoirs but are blocked from additional rounds of replication by the drugs. Several approaches are under exploration for reactivating latent virus with the hope that this will allow elimination of the latent reservoir.